Lachancea thermotolerans fermentative metabolism is enhanced by chitosan under winemaking conditions - Vicente, Javier (Elsevier, 2025)
Wine industry is currently exploring different alternatives to sulphur dioxide as an antimicrobial agent, and chitosan is emerging as a highly promising option due to its multiple applications. In the context of climate change, the use of Lachancea thermotolerans to regulate pH and acidity levels during fermentation has become a promising alternative to other physicochemical approaches. This work analysed the impact of chitosan in sequential-mixed fermentations between L. thermotolerans and Saccharomyces cerevisiae. The presence of chitosan significantly affected the overall fermentation kinetics, resulting in faster fermentations and lower residual sugars, all without an increase in ethanol production. Wines produced under these conditions exhibited increased lactic acid levels (up to 50% more) and decreased malic acid content. This differences significantly influenced final pH (around 0.2 units) and acidity content (up to 1.65 g/L more) when compared to sulphur dioxide-supplemented controls. Chitosan also notably affected to other fermentative by-products, such as glycerol, contributing to improved wine complexity and quality. The addition of chitosan in wine fermentation impacted not only the fermentative performance of key non-Saccharomyces yeasts but the overall quality of the final product. This study provides new insights into the different effects of chitosan during the wine fermentative process.